2020
DOI: 10.1039/d0ob00444h
|View full text |Cite
|
Sign up to set email alerts
|

A domino annulation approach to 3,4-diacylpyrrolo[1,2-a]pyrazines: decoration of pyrazine units

Abstract: A new one-pot, sequential three-component access to 3,4-diacylpyrrolo[1,2-a]pyrazine was achieved from the reaction of an α-haloketone, azide, and N-substituted pyrrole-2-carboxaldehyde under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In 2013, we published a domino Knoevenagel condensation–intramolecular aldol condensation sequence to enable access to a wide range of indolizines 2 with densely functionalized pyridine units (Scheme a) . In the course of our continued study on the construction of novel N -fused heterocyclic chemical spaces from pyrrole derivatives such as 1 , we hoped to establish a highly efficient diversity-oriented synthetic route to 4 , utilizing a sequential one-pot three-component coupling reaction as shown in Scheme b. We reasoned that β-ketonitrile 3 generated in situ from the reaction of α-haloketone with cyanide would react with 1 to afford 4 and/or 4′ via a Knoevenagel condensation–intramolecular aldol cyclization cascade process .…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, we published a domino Knoevenagel condensation–intramolecular aldol condensation sequence to enable access to a wide range of indolizines 2 with densely functionalized pyridine units (Scheme a) . In the course of our continued study on the construction of novel N -fused heterocyclic chemical spaces from pyrrole derivatives such as 1 , we hoped to establish a highly efficient diversity-oriented synthetic route to 4 , utilizing a sequential one-pot three-component coupling reaction as shown in Scheme b. We reasoned that β-ketonitrile 3 generated in situ from the reaction of α-haloketone with cyanide would react with 1 to afford 4 and/or 4′ via a Knoevenagel condensation–intramolecular aldol cyclization cascade process .…”
Section: Introductionmentioning
confidence: 99%
“…Further, only compounds 37a and 37b showed high potency against all Akt isoforms. Dagar et al [120] reported the one-pot synthesis of 3,4-diacylpyrrolo[1,2a]pyrazine by the reaction of an α-haloketone, azide, and N-substituted pyrrole-2-carboxaldehyde. This investigation reveals that only compound (38) showed potential in vitro anticancer activity against oral adenosquamous carcinoma and triple-negative human breast cancer cells in comparison with standard capecitabine.…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…α-Azidoketones and esters have been utilized in the synthesis of a large number of six membered nitrogen heterocycles such as pyridines, pyrimidines, pyrazines, and aza-pyrimidinones. [83][84][85][86][87][88][89][90][91][92][93][94][95][96]…”
Section: Six Membered N-heterocycles From α-Azidoketones/estersmentioning
confidence: 99%
“…After imine-enamine tautomerization, intramolecular condensa- Recently, Kim and co-workers reported annulations of αazidoketones and N-substituted pyrrole-2-carboxaldehyde to yield 3,4-diacylpyrrolo[1,2-a]pyrazine 276 using catalytic amounts of CuI and i-Pr 2 NH as base (Scheme 53). [95] In the presence of CuI, i-Pr 2 NH mediated deprotonation of α-azidoketones lead to the formation of a chelated imine 245. The nucleophilic addition between aldehyde and imine leads to the formation of an intermediate 275 which after dehydration and aromatization leads to the desired diacylpyrrolo[1,2-a]pyrazine 276.…”
Section: Pyrazinementioning
confidence: 99%